An initial assessment of economic impacts and operational challenges for the tourism & hospitality industry due to COVID-19 - Andreas Thams; Nicola Zech; David Rempel; Albert Ayia-Koi (IUBH Internationale Hochschule, 2020)
The tourism and hospitality industry currently faces one of its most serious operational, commercial, and financial crises as a result of the worldwide spread of COVID-19. Both destinations and source markets are substantially affected and have suspended operations and commercial activities. Major market players in all areas of the touristic value chain, i.e., airlines, tour operators, hotels, cruise lines, and retailers, have either minimized or even completely stopped their production for an undefined period of time, resulting in the sudden and total cut-off of their revenue streams. This paper will comprehensively highlight in an initial assessment economic impacts and operational challenges for the tourism and hospitality industry caused bv the from COVID-19 crisis. General and mostly European-centered perspectives are supplemented by an African insight represented by a Ghanaian case-study.
Keywords: 650; COVID-19; tourism industry; travel industry; hospitality management; economic impact; operational challenges; crisis management